Evaluation of N-doped carbon for the peroxymonosulfate activation and removal of organic contaminants from livestock wastewater and groundwater. Issue 16 (29th March 2022) - Cai, Shu; Zuo, Xiaoxue; Zhao, Haiyan; Yang, Shengjiong; Chen, Rongzhi; Chen, Liwei; Zhang, Ruihong; Ding, Dahu; Cai, Tianming
Abstract : Polydopamine coating significantly prevents N loss during the pyrolysis of g-C3 N5 . N-Doped carbon drives the organics oxidation by electron-transfer between the surface-activated PMS and organic contaminants. Abstract : Elimination of trace organic contaminants from complex environmental matrices is of great importance for environmental remediation. Herein, the efficient removal of trace antibiotics and hydrocarbons from livestock wastewater and contaminated groundwater was realized using a newly prepared N-doped carbon catalyst (PDA–gCN-1.0). Specifically, carbon nitride (g-C3 N5 ) was synthesized and coated with polydopamine (PDA), which could inhibit the N-loss during the thermal treatment, as well as serve as an exogenous nitrogen source. The resultant metal-free catalyst PDA–gCN-1.0 (dopamine : g-C3 N5 = 1 : 1) possessed abundant N configurations, and could effectively activate peroxymonosulfate (PMS) and peroxydisulfate (PDS). Typically, with 50 mg L −1 PDA–gCN-1.0 and 1 mM PMS, sulfamethoxazole (SMX, 10 mg L −1 ) could be completely oxidized within 5 min ( k = 1.691 min −1 ), surpassing most state-of-the-art catalysts ( e.g., Co3 O4 nanoparticles, graphene oxide, activated carbon). The oxidation process was found to be dominated by the nonradical mechanism, instead of the radical species. More specifically, electron-transfer between organics and high potential C–PMS* complexes played a significant role. The transformation pathways of SMX were proposed based on the identified intermediate products, and the toxicity of the corresponding products were predicted using the ECOSAR program. Finally, the eliminations of trace antibiotics (from livestock wastewater) and hydrocarbons (from contaminated groundwater) were investigated by the developed PDA–gCN-1.0/PMS process. The much higher removal efficiencies of target organic contaminants than TOC removal efficiencies clearly demonstrated the satisfactory selectivity of the nonradical-dominated PDA–gCN-1.0/PMS process. The reduced inhibition rate of E. coli confirmed that the developed advanced oxidation process was effective for the toxicity reduction of the wastewater. The findings of this work would shed new light on the applications of metal-free catalysts in environmental remediation.